Evaluation Of AKHLAK Core Values Implementation At PT XYZ - Imada Darel Natanel (Jurnal Ilmiah Wahana Pendidikan, 2023)
PT XYZ won the AKHLAK award 2. Based on this phenomenon, this study aims to evaluate the implementation of AKHLAK conducted by PT XYZ so that it can be successful in winning the AKHLAK award. This research was conducted on the implementation of PT XYZ for the period 2021 to June 2022. The type of research is qualitative and the collection technique uses document studies and in-depth interviews. The results of data collection in the form of AKHLAK implementation at PT XYZ were compared with the best practice of implementing core values ​​and analyzed descriptively. The results of the analysis obtained, PT XYZ has implemented 4 aspects of AKHLAK best practice (culture attributes and leadership lays the foundation, levers of change system, new ways to gather and learn, and activating managers by leveraging listening system. However, there is a lack of implementation in the fifth aspect, namely the aspect of HR's evolving role and structure